On the Multi-hazard Risk Assessment of Urban Areas: Identification and Analysis of Exposure and Physical Vulnerability Indicators - Xofi, Maria (2022)
The development of integrated decision-support tools, able to assess multiple hazards at the regional and local scales, is a fundamental step to enhance the preparedness of urban areas to mitigate present and future risks arising from climate change. Understanding multi-hazard risk can help prioritize resilience-increasing actions and disaster prevention measures and form the basis for exploring institutional adjustments that improve stakeholders’ capacities to manage risk. Within this framework, the present research work aims to identify and analyze a set of exposure and buildings’ vulnerability indicators to be used as input to a multi-hazard risk assessment methodology. Exposure is to be measured using a dimensionless score resulting from the quantitative identification of the elements at risk. Regarding the physical vulnerability of buildings, it is to be evaluated on a hazard-by-hazard basis using a large-scale parametric-based vulnerability assessment approach. Finally, the obtained exposure and physical vulnerability indicators are to be put together in order to create different data layers, which are then used to identify hotspot risk areas. The Metropolitan Area of Lisbon, Portugal, is used as a pilot study area to discuss the applicability and potential of the proposed indicators.